Association of GRIN2A (rs387906637) Gene Polymorphism with Epilepsy Susceptibility - Jawad Hameedi, Akram; Mohammed Saud, Asmaa (Iraqi Journal of Science, 2021)
The aim of this study was to investigate the correlation between GRIN2A rs387906637 polymorphism and susceptibility to epilepsy. Blood samples were collected from 85 volunteers, dividing into 60 epilepsy patients (34 males and 26 females) and 25 healthy subjects (19 males and 6 females).The DNA was extracted and GRIN2A rs387906637 polymorphism was analyzed by Real-time PCR using two probes and primers. The results showed no significant differences between patients and control samples; therefore, there are no allelic and genotypic correlations of this SNP with epilepsy. This study indicated that GRIN2A rs387906637 polymorphism is not a risk factor for epilepsy in the studied set of patients.